Short-Chain Fructo-oligosaccharide and Inulin Modulate Inflammatory Responses and Microbial Communities in Caco2-bbe Cells and in a Mouse Model of Intestinal Injury. Issue 11 (20th August 2014) - Johnson-Henry, Kathene C.; Pinnell, Lee J.; Waskow, Alexandra M.; Irrazabal, Thergiory; Martin, Alberto; Hausner, Martina; Sherman, Philip M.
Abstract: Background: Few studies have focused on the ability of prebiotics to prevent pathogen-induced cellular changes or alter the composition of the intestinal microbiota in complimentary relevant cell and animal models of inflammatory bowel disease. Objective: The objective of this study was to determine if pretreatment with inulin and a short-chain fructo-oligosaccharide (sc-FOS) prevents enterohemorrhagic Escherichia coli (EHEC) O157:H7 infection in Caco2-bbe epithelial cells and what effect 10% wt:v sc-FOS or inulin has on C57BL/6 mice under sham conditions or pretreatment with prebiotics before Citrobacter rodentium infection (10 8 colony-forming units). Methods: Actin rearrangement and tight junction protein (zona occludin-1) were examined with immunofluorescence. Barrier function was assessed by a fluorescent probe and by measuring transepithelial electrical resistance (TER). Alterations in cytokine gene expression and microbiome were assessed with quantitative reverse transcriptase-polymerase chain reaction and fluorescence in situ hybridization. Short-chain fatty acids (SCFAs) were measured by GC. Results: sc-FOS added to monolayers altered actin polymerization without affecting TER or permeability to a fluorescein isothiocyanate (FITC) probe, whereas inulin increased TER ( P < 0.005) and altered actin arrangement without affecting FITC permeability. Neither prebiotic attenuated EHEC-induced decreases in barrier function. Prebiotics increased interleukin 10 ( Il10 ) and transforming growth factor-β ( Tgf β) cytokine responses alone ( P < 0.05) or with EHEC O157:H7 infection ( P < 0.05) in vitro. Increases in tumor necrosis factor-α ( Tnfα ) ( P < 0.05) and decreases in chemokine CXC motif ligand 8 ( Cxcl8 ) ( P < 0.05) expression were observed with prebiotic treatment prior to EHEC infection. No differences were noted in barrier function or cytokine responses in the absence or presence of C. rodentium in vivo. Alterations in microbiome were evident at 6 d and 10 d postinfection in treatment groups, but a change in C. rodentium load was not observed. Inulin and sc-FOS ( P < 0.05) increased fecal SCFAs in the absence of infection. Conclusion: This study provides new insights as to how prebiotics act in complementary in vitro and in vivo models of intestinal injury.